System Thinking Urgency in Public Policy Analysis - Agustina, Heryani; Sutarih, Ayih (International Journal of Psychosocial Rehabilitation, 2020)
Systems thinking is a process of thinking to understand a problem as a whole. Systems thinking is very important in the analysis of public policy because through systems thinking, it can understand complex policy issues thoroughly so that appropriate public policy can be taken to overcome these problems. Systems thinking in making a public policy in the form of legislation appears from the contents of its academic manuscript. However, many Academic Manuscripts are made haphazardly, so that public policies are made unable to overcome problems or even cause new problems.